2007
DOI: 10.1136/thx.2006.061358
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune activation in neutrophilic asthma and bronchiectasis

Abstract: Background: The role of the innate immune system in the pathogenesis of asthma is unclear. Activation of innate immune receptors in response to bacterial lipopolysaccharide, viral infection and particulate matter triggers a pre-programmed inflammatory response, which involves interleukin (IL)8 and neutrophil influx. The inflammatory response in asthma is heterogeneous. Aim: To test the hypothesis that innate immune activation may be a relevant inflammatory mechanism in neutrophilic asthma where IL8 levels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
292
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(317 citation statements)
references
References 45 publications
20
292
0
5
Order By: Relevance
“…Similarities have previously been found between ME/NA and NA in terms of the level of innate immune mediators such as IL-8 in induced sputum. 6 However, our recent sputum gene expression study showed that subjects with ME/NA were predominantly clustered with EA rather than NA. 12 Recent work has shown that corticosteroid treatment can induce a sputum neutrophilia, 13 raising the possibility that ME/NA represents corticosteroid-overtreated EA.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Similarities have previously been found between ME/NA and NA in terms of the level of innate immune mediators such as IL-8 in induced sputum. 6 However, our recent sputum gene expression study showed that subjects with ME/NA were predominantly clustered with EA rather than NA. 12 Recent work has shown that corticosteroid treatment can induce a sputum neutrophilia, 13 raising the possibility that ME/NA represents corticosteroid-overtreated EA.…”
Section: Discussionmentioning
confidence: 89%
“…6 An important aspect of lung innate immune responses is the production of antimicrobial proteins such as the a-and b-defensins. 14 Defensins are small arginine-rich cationic peptides with antimicrobial activity against a broad range of pathogens including bacteria, fungi and some enveloped viruses, and exert this antimicrobial effect through membrane permeabilisation of the microbe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma involves a heterogeneous inflammatory response, with activation of both the acquired and the innate immune systems (Simpson et al, 2007). Innate immune activation leads to an IL-8-mediated neutrophilic airway inflammation (Simpson et al, 2007).…”
Section: Dietary Fat Inflammation and Lung Functionmentioning
confidence: 99%
“…IL-6 is a potent inducer of neutrophil responses, which are closely linked to the development of airflow obstruction (AFO) (Shaw et al, 2007). IL-6 and neutrophil responses are also typical features of innate immune activation, which can be persistently activated in neutrophil mediated airway diseases (Simpson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%